1991
DOI: 10.1177/0267323191006004005
|View full text |Cite
|
Sign up to set email alerts
|

Resisting American Hegemony: A Comparative Analysis of the Reception of Domestic and US Fiction

Abstract: Recent qualitative audience research on the reception of US fiction abroad has been presented as a valuable new perspective in studying the world-wide appeal and impact of American programming. However the concentration on the decoding of US fiction alone (usually Dallas) has stimulated an essential and decontextualized position on these issues. The results from a comparative reception analysis (comparing the reception of an American fiction programme and a similar domestic one by respondents in a small Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Reception researchers have concluded that audiences' own cultural experiences tend to provide them with the capacity to resist cultural imperialism through television (for examples see Schroder, 1988;Katz and Liebes, 1990). Some scepticism toward the way in which these studies romanticise the notion of the active viewer is necessary, together with acknowledgment of the fact that little is known about the long term nature of this resistance (Biltereyst, 1991). But this does indicate the need for comparative analyses of how home produced and imported dramas are received and interpretatively 'processed' by viewers.…”
Section: Assumptions About 'Problem' Viewers and 'Problem' Programsmentioning
confidence: 99%
“…Reception researchers have concluded that audiences' own cultural experiences tend to provide them with the capacity to resist cultural imperialism through television (for examples see Schroder, 1988;Katz and Liebes, 1990). Some scepticism toward the way in which these studies romanticise the notion of the active viewer is necessary, together with acknowledgment of the fact that little is known about the long term nature of this resistance (Biltereyst, 1991). But this does indicate the need for comparative analyses of how home produced and imported dramas are received and interpretatively 'processed' by viewers.…”
Section: Assumptions About 'Problem' Viewers and 'Problem' Programsmentioning
confidence: 99%
“…More recent flow studies have demonstrated that, despite the prevalence of American products in the media supply, audiences often show Cultural Globalization and the Global Spread of English 329 a preference for local programs (e.g. Biltereyst, 1991Biltereyst, , 1992Chadha and Kavoori, 2000;McMillin, 2001;Straubhaar, 1991). Secondly, even if a foreign media product is actually consumed, this does not mean that audiences also adopt the culture in which it was created (Ferguson, 1992).…”
Section: Dependency Theory and Cultural/media Imperialismmentioning
confidence: 99%
“…In the 1990s, especially, several studies demonstrated how audiences interpret and/or adapt foreign or global cultures in ways which suit their own local and/or national cultures (e.g. Bennett, 1999;Biltereyst, 1991;Gillespie, 1995).…”
Section: Active Audience and Hybridizationmentioning
confidence: 99%
“…Some case studies dealt with the reception of US fiction programmes by several types of ethnically different groups of respondents (for example Herzog 1986;Liebes & Katz 1990), while other studies analysed the various ways in which specific respondents received US and domestic programmes (for example Biltereyst 1991;Hjort 1986).…”
Section: A Relativist Voice In the International Communication Debatementioning
confidence: 99%
“…Since the mid-1980s, these 'new' audience studies have quickly grown into a quite 'popular' approach treating a wide range of topics such as the social functioning and understanding of specific media genres (for example Jensen 1986 on news; Livingstone 1990 on soaps), their ways of mediating specific social issues (for example Corner et al 1990 on the nuclear debate), the determining influence of contextual factors on understanding media reception (for example Biltereyst 1991 on language and cultural proximity; Liebes & Katz 1990 on ethnicity), and of demographic typologies (for example Morley 1980 on social class and gender).…”
Section: Introductionmentioning
confidence: 99%